Urgensi Tasawuf di Tengah Pandemi Covid - Rahmah Rahmah (UIN Antasari Banjarmasin, 2021)
The spread of Covid-19 continues to develop rapidly and widely, which greatly affects human social life in various aspects, one of which is human behavior. Of course this is not a simple problem of the Corona virus outbreak testing all capacities as humans by facing uncertainty, even though it is believed that Allah Swt must certainly create disease and of course the cure.Every human being will experience problems in his life, including when he is going through difficult, anxious and pessimistic times as well as depression as a result of the Covid-19 pandemic. The problem is whether every human being is able to survive these problems. In the perspective of Sufism, the problems of life are very much influenced by the form of acceptance and interpretation of the events experienced, when a person is not able to properly understand the meaning of life's trials and is unable to accept Allah's provisions for His creatures, life's problems will be even heavier. For those who are aware and have knowledge, will try to solve it either independently or by asking for help from an expert. One of the alternatives to solve life's problems is by doing tasawuf. How a Muslim responds to the Covid-19 outbreak there are at least three things that a Muslim needs to do in facing tests like this, namely sincerity, patience, and gratitude.